THE ROLE OF LOCAL GOVERNMENT IN DISASTER MANAGEMENT (Study on the Regional Disaster Management Agency in Flood Disaster Mitigation in Samarinda City) - Khaerani, Thalita (Department of Government, FISIP, Universitas Padjadjaran, 2022)
<p class=